The extract of Jeruju plant for anti-inflammatory: A literature review using nursing perspective - Nia Afifatul Ulya; Heni Setyowati Esti Rahayu; Prasojo Pribadi (Universitas Muhammadiyah Magelang, 2022)
Jeruju plant has some benefits in reducing symptoms of a particular disease. However, there is little discussion about plants in nursing. Therefore, the literature review aims to identify the effectiveness of Jeruju plant extract as an anti-inflammatory. The method used is a literature review integrating electronic databases such as Google Scholar and ScienceDirect. The keywords used in Indonesian are